KONTRIBUSI KOMPETENSI PERAWAT DAN KEPUASAN KERJA SERTA IMPLIKASINYA TERHADAP KINERJA PERAWAT RUMAH SAKIT UMUM DAERAH DI SAMARINDA DAN BALIKPAPAN - sukamto, edi sukamto; Rasmun, Rasmun (JURNAL MEDIA KESEHATAN, 2020)
Regional General Hospital requires nurses who are able to do more than just formal tasks and are willing to give good performance. Nurses want better performance to carry out their functions. Achieving optimal performance can be done if the nurse has competence, besides that nurse satisfaction is also a determining factor for Nurse's performance. The purpose of this study was to determine the effect of competence on job satisfaction and performance. The population in this study was the Managing Nurse. The sampling technique is Purpossive Sampling. The sample in this study were all nurses working in the inpatient ward of the IA Moeis regional general hospital in Samarinda, the Beriman regional general hospital in Balikpapan, totaling 128 nurses. This research was analyzed using the WarpPLS program. The results of this study indicate that competence has a significant positive effect on satisfaction. Competence gives an insignificant negative effect on performance. Satisfaction gives a significant positive effect on performance. Recommendations in this study IA Moeis Regional General Hospital Samarinda and the Beriman regional general hospital in Balikpapan are expected to continue to make regular improvements with nurses about optimizing the achievement of competencies both individually and collectively in order to achieve goals. IA Moeis Regional General Hospital Samarinda and the Beriman regional general hospital in Balikpapan are expected to provide a fair and objective assessment of the quality of work so as to encourage satisfaction with the increase in nurse performance